Inositol derived crown ethers: effect of auxiliary protecting groups and the relative orientation of crown ether oxygen atoms on their metal ion binding ability - Dixit, Shailesh S.; Shashidhar, Mysore S. (Tetrahedron, 2008)
The binding constants of crown ethers prepared from tetra-O-substituted myo- and scyllo-inositol derivatives and 2-O-substituted myo- and scyllo-inositol-1,3,5-orthoformates, with metal picrates show that the O-substituents and the relative orientation of the crown ether oxygen atoms contribute significantly to the binding of crown ethers with metal ions. In particular, the binding efficiency of myo-inositol derived crown ethers to silver and potassium ions could be enhanced by introducing benzyl ethers in the inositol ring. Hence binding efficacy and selectivity of metal ions to inositol derived crown ethers can be tuned by varying substituents on the myo-inositol ring and/or the relative orientation of crown ether oxygen atoms. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: crown ether; Cyclitol; Inositol; ligand; metal complex; supramolecule